Prova Brasil : alguns fatores determinantes da qualidade de ensino de matemática das escolas públicas do município de Maringá-PR - Santos, Valdirene Maria dos (2013)
This study aims at studying Prova Brasil in order to identify some of the decisive factors to establish a good quality Mathematics instruction, particularly to students in elementary public schools in the city of Maringá. A brief education historical background opens our study being then followed by a discussion on both education and instruction quality.Some official indicators from public policies for educational assessment are presented, such as Prova Brasil, SAEB (Elementary Education Assessment System); instruction quality indicator, IDEB (Elementary Education Development Rate) and the international assessment PISA (International Program for School Performance Assessment); we sequently report data revealed from those indicators and assessments from 2005 to 2011. We investigate the relationship between economic capital and family culture and performance in Mathematics, taking into account only students in the fifth grade. In order to widely write on the subjetc we briefly introduced the concepts of Cultural, Economic and Social Capital under the view of sociologists such as Pierre Bourdieu and James Coleman whose theories supported the qualitative content. We present the results of our studies on two city schools seeking to establish factors that could not be statistically detected. Our main result points that the higher the levels for Cultural, Economic and Family Capitals the higher the average marks recorded for Mathematics, identifying a positive association between such variables and school performance. We used microdata from ?Prova Brasil? 2011 provided by INEP (Anísio Teixeira National Institute of Research in Education) and in order to treat such data we used SAS software.